Book Review Essay: The Parentheses Have Been Blown Apart: Misrecognition in Late Capitalism, on “Clinical Introduction to Lacanian Psychoanalysis” by Daniéle Brillaud - Cassandra Seltman (EJP import test, 2021)
Review of A Clinical Introduction to Lacanian Psychoanalysis. Routledge, 2020, Pp. 286